2022
DOI: 10.1021/acs.jmedchem.2c01320
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Potent CYP4Z1 Inhibitor Attenuating the Stemness of Breast Cancer Cells through Lead Optimization

Abstract: Pharmacological targeting cancer stem cells are emerging as a novel therapeutic modality for cancer treatment and prevention. Human cytochrome P450 enzyme CYP4Z1 represents a promising target for its potential role in attenuating the stemness of breast cancer cells. In order to develop potent and selective CYP4Z1 inhibitors, a series of novel N-hydroxyphenylformamidines were rationally designed and synthesized from a pan-CYP inhibitor HET0016. CYP4Z1 inhibitory activities of the newly synthesized derivatives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This 'suicide gene' strategy was further refined recently by Hanenberg's group for application in adoptive T-cell therapies using a highly active modified human CYP4B1 (Roellecke et al, 2016). Today, attention in this area has turned increasingly towards CYP4Z1 as the target for enzyme inhibitors (Kowalski et al, 2020 a ;Machalz et al, 2021;Yuan et al, 2022), and potentially as a protoxin activating CYP in breast cancer. There and back again indeed!…”
Section: Discussionmentioning
confidence: 99%
“…This 'suicide gene' strategy was further refined recently by Hanenberg's group for application in adoptive T-cell therapies using a highly active modified human CYP4B1 (Roellecke et al, 2016). Today, attention in this area has turned increasingly towards CYP4Z1 as the target for enzyme inhibitors (Kowalski et al, 2020 a ;Machalz et al, 2021;Yuan et al, 2022), and potentially as a protoxin activating CYP in breast cancer. There and back again indeed!…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CSCs have been found to have immunomodulatory activity as CSCs have been shown to exhibit the immunotherapeutic resistance. According to these characteristics, CSCs play an irreplaceable role in the treatment of malignant tumors as our previous studies have shown targeting CSCs can significantly suppress tumor migration, invasion, and drug resistance [32][33][34]. Epigenetics plays an important role in maintaining the above biological characteristics of CSCs, which refers to the phenomenon that the DNA sequence has not changed but the traits have heritable changes.…”
Section: The Effects Of M 6 A-rna Modification On Csc Progressionmentioning
confidence: 99%